Immaterial public order in French public law - Peyroux-Sissoko, Marie-Odile (Journal of the Belarusian State University. Law, 2020)
As a central notion of the relationship between the state and individuals, public order implemented by the administrative police is traditionally identified as material. Essential to the balance between maintaining social peace and guaranteeing individual rights and freedoms, it is particularly used when security is at stake. Recent legislation (in the lato sensu) on states of emergency recalls this. But public order is not only material, limited to public security, tranquility and health. A classic notion of public law, public order is constantly evolving. It is indeed possible to draw from various scattered phenomena the existence of an immaterial public order whose emergence and use are intended to respond to imbalances that have appeared in the rule of law. Allowing, in particular, the protection of objective values on the basis of which society is ordered, immaterial public order aims to rebalance the relationship between the collective and the individual. In this sense, it is a functional concept. It is thus possible to define immaterial public order and to construct a legal regime adapted to it. Impotent to restrict freedoms in private life, it is expressed in the public space to which it is confined, which limits the risks of intrusion by the state. It can be seen as an autonomous notion. This formalisation makes it easier to identify immaterial public order. Above all, it suggests that it could become permanently established in the French legal system.